REACAO TECIDUAL A ALGUNS TIPOS DE FIOS DE SUTURA. AVALIACAO HISTOLOGICA EM RATOS - De Castro, H. L.; Okamoto, T.; De Castro, A. L. (My University, 1974)
In 37 male albino rats the behavior of tissues to different types of suture materials, such as cotton, nylon, and polyester was studied. The animals were divided into 2 groups. The first group consisted of 16 animals with superficial sutures. These materials were passed across the skin of the dorsum concerning the subcutaneous plain. No incision was made. The animals were killed 1,2,3, and 6 days postoperative. Group 2 consisted of 21 animals with deep sutures into the flat muscle. These animals were killed 1,2,3,6,10,20, and 60 days postoperative. Cotton sutures provoked an intense inflammatory reaction with abscess formation around both the superficial and deep sutures; the giant cell reaction was more evident when cotton sutures were employed; earlier proliferation of fibroblasts and capillaries was observed in the case of nylon sutures, and with the latter, both inflammatory and giant cell reactions were less significant.
Tissue reaction to some suture materials. Histologic evaluation in rats